Acceleration of Blue Swimming Crab (Portunus pelagicus) Larval Development by Phytoecdysteroid - Ahmad, Fakhirah; Fujaya, Yushinta; Trijuno, Dody Dharmawan; Aslamyah, Siti (Indonesian Aquaculture Society (MAI), 2015)
Phytoecdysteroid is a mimic hormone like molt regulating hormone in arthropoda and crustacea. This research aims to investigate the response of Portunus pelagicus larvae on various doses of vitomolt enrichment in predigested artificial diet. Four doses of vitomolt (0; 4; 40; 400 mg/100 g artificial diet) were used in this research. Larval development and survival rate were measured The results showed that the larvae development rate was increased in congruent with the dose of vitomolt. However, highest survival rate was found on 4 mg vitomolt/100 g artificial diet (P>0.05). Based on regression analysis, it is estimated the optimal dose of vitomolt for larval development rate and survival rate was about 23 mg/100 g of artificial diet. Vitomolt application in artificial diet could be used to accelerate the larval development rate in blue swimming crab. Keywords: Portunus pelagicus, phytoecdysteroid, artificial diet, survival, larval development